PROBLEMATIKA DAN TEKNIS PENYELENGARAAN PEMILIHAN KEPALA DAERAH PADA MASA PANDEMI COVID 19 - Sarjan Sarjan; Kemal AL Kindi Mulya; Siti Chadijah (Program Studi Hukum Universitas Pamulang, 2020)
Indonesia is a country that adopts a democratic system. In carrying out general elections it is a necessity that has been mandated by the 1945 Constitution in accordance with the sounds of Article 22E Paragraphs (1), (2), (3), (4), (5) and (6). This requirement makes it a condition in selecting Regional Representative Council Members. The government, through Perppu No. 2 of 2020, remains unmoved that the regional head election will be held on 9 December 2020. Apparently this year 2020 has become a year unlike previous years, because in this year specifically Indonesia is in the Covid-19 pandemic and broadly Covid-19 has become a world epidemic today. Initially the 2020 elections will be held on September 23, 2020 to select 9 governors, 224 regents, and 37 mayors simultaneously. In conducting this analysis, the author uses a juridical normative approach, which is an approach aimed at studying the principles of law, and legal schemes. The discussion that the author will elaborate on is how the election is based on laws and regulations, also what kind of problems will arise in the holding of the elections during a pandemic, and what kind of implementation techniques, In order to know the limits of the application of the law to elections in the Covid-19 pandemic.